The Writing Methodology of Mi‘yār al-‘Ilm fī Fann al-Manṭiq - Towpek, Yaman; Salleh, Kamarudin (Jurnal Usuluddin, 2017)
Mi‘yār al-‘Ilm fī Fann al-Manṭiq of al-Ghazālī is the first book on Islamic logic. But the specific, comprehensive and exclusive study on the essence of its scientific contents and its significance in developing scientific thinking has never been done. Thus this study investigates the methodology of Mi‘yār writing. This qualitative study uses content analysis method. The data which were collected using the documentation has been analyzed using the inductive, deductive, and comparative methods. The process of analysis of logic in Mi‘yār be done using methods of textual analysis or textual content analysis and constant comparison. It is because of this study is a textual study. This study found that Mi‘yār written by two objectives. Firstly; to provide an understanding on the methodologies of thinking and researching, and explain the rules of constructing syllogisms and analogies. Secondly; to review the matters which have been written in Tahāfut. The study also found that al-Ghazālī wrote Mi‘yār using atleast 18 methodologies of writing. Therefore Mi‘yār should be a fundamental source of learning logic and methods of thinking of Muslims either at high school or university. Hence the constant, thorough and deep study on the content of Mi‘yār is very significant and has high impact. But the dissemination of the findings of this study is the next action that should be realized.